Beyond the neonatal period: unmasking late presenting congenital diaphragmatic hernia: a case report - Bora, Rajib; Bharadwaj, Arunima; Jain, Nitin (International Surgery Journal, 2025)
Congenital diaphragmatic hernia (CDH) is a common neonatal emergency characterized by a defect in the diaphragm causing abdominal organs to herniate into the thoracic cavity. Most cases of CDH present in the neonatal period with severe respiratory distress; however, a proportion of CDH cases present beyond the neonatal period, termed as late-presenting CDH. Being relatively uncommon compared to neonatal CDH, late-presenting cases pose unique diagnostic and therapeutic challenges. In this case report we present an uncommon case of late presenting CDH where posterior lip of diaphragm was completely absent with underdeveloped anterior lip, managed successfully using local tissues and intricate surgical manoeuvres lead to favourable outcome.